Clinical management of incidental findings on pelvic adnexal masses - Dias, Daniel Spadoto [UNESP]; Bueloni-Dias, Flávia Neves [UNESP]; Delmanto, Armando [UNESP]; Tonon, Ângela Favorito Santarém [UNESP]; Tayfour, Najla Mohamad; Traiman, Paulo [UNESP]; Dias, Rogério [UNESP] (FapUNIFESP (SciELO), 2015)
Due to widespread use of pelvic and transvaginal ultrasound in routine gynecological evaluation, the incidental finding of adnexal masses has led to discussions about management in asymptomatic patients regarding the risk of ovarian cancer. Transvaginal ultrasonography remains the modality of choice in the evaluation of suspicious characteristics. The combined analysis of ultrasound morphological parameters with Doppler study, serum carcinona antigen 125 and investigation of a symptom index may improve diagnosis. Surgical approach should be considered whenever there are suspicious images, rapid growth of cysts, changes in the appearance compared to the initial evaluation or when the patient has symptoms. Future studies on genetic and molecular mechanisms may help explain the pathophysiology of ovarian cancer, improving early diagnosis and treatment.
Keywords: Adnexal diseases; CA-125 antigen; Ovarian cysts; Ovarian neoplasm's; Ultrasonography